OBSERVATIONS OF REGULARITIES IN TOKAPUS OF SOME KEROS OF THE COLONIAL PERIOD - Nagy, Katalin (2009)
The present article does a study of the tokapus from the description of topics and colors in carpets, carpets, ceramics, queros, etc., and also it tries to describe the informative content in order to understand the cultural environment and the relations that the handling of this information implies.